PWE-060 Polypectomy Practices In The English Bowel Cancer Screening Programme. (9th June 2014) - Din, S; Ball, A; Taylor, EJ; Rutter, M; Riley, S; Johal, S
Abstract : Introduction: Most polyps are <10 mm in size and a range of polypectomy techniques are available with wide variations in practice. We aimed to examine the techniques employed for removal of <10 mm polyps in relation to polyp characteristics, completeness of excision, safety and changes over time. Methods: Data relating to removal of polyps <10 mm between Jan 2010 and Dec 2012 were retrieved from the national Bowel Cancer Screening Programme (BCSP) database. Categorical data was compared using x 2 . Results: 147174 polyps were removed during 62679 colonoscopies. A range of techniques was used (cold biopsy forceps (CBF) 19.7%, cold snare (CS) 22.1%, hot biopsy forceps (HBF) 12.2%, hot snare (HS) 35.1%, EMR 10.9%). EMR was used more frequently in the right colon compared to the left (14.3 vs. 8.3%, OR = 1.84, 95% CI: 1.78–1.90). Most pedunculated polyps were removed using HS; this was lower in the right vs. left colon (69.6 vs. 88.3%, OR = 0.30, CI: 0.28–0.33). CS was most common for non-pedunculated polyps in the right colon (29.8 vs. 19.0% in left, OR = 1.81 CI: 1.76–1.85); whereas most common in the left colon was HS (34.8 vs. 22.5% in right, OR = 1.84 CI: 1.79–1.88). Surgeons were more likely than physicians to use diathermy irrespective of site or morphology (65.6 vs. 56.5%, OR = 1.46 CI: 1.43–1.5). In 60% of polyps removed completeness of excision was not histologically assessable. 21.2% were completely excised, 5.8% incomplete and 13% not stated. For non-pedunculated polyps, histologically-confirmed complete excision was more common after EMR (23.4 vs. 6.2%, OR = 1.16, CI: 1.08–1.25) compared to other techniques (CBF 17.7%, CS 15.1%, HBF 19.1%, HS 21.5%); for pedunculated polyps it was more common after EMR (42.3%) and HS (42.0%). Complications were rare for colonoscopies (45227) where only polyps <10 mm were removed. 12 (0.03%) bleeding episodes required transfusion; rates for single and multiple polypectomy cases were 0.01 and 0.04% respectively (OR = 5.01, CI: 1.10–22.8). The HS technique was most commonly used. There were 16 (0.04%) perforations; 0.02% for single vs. 0.05% for multiple polypectomies (OR = 2.20, CI: 0.77–6.34, p = 0.13). No technique dominated for single compared with HS for multiple polypectomies. Between 2010 and 2012, use of CBF, CS and EMR increased, whereas HBF and HS decreased (p < 0.01) Conclusion: The removal of polyps <10 mm within the BCSP is safe, but histological evidence of completeness of excision is poor with all techniques. Wide variations in practice reflect the lack of evidence guiding these decisions, although use of cold resection techniques has increased over time Disclosure of Interest: None Declared.